Outcome of Open Diaphyseal Tibial Fracture Managed with Unreamed Intra Medullary Inter Locking Nail (Journal of Pakistan Orthopaedic Association, 2016)
Objective: To determine the outcome of unreamed intra medullary inter locking nail in management of open tibial diaphyseal fracture in terms of union. Methods: This descriptive case series study was conducted from July 2011 to June 2012. Adult patients of either sex with tibial diaphyseal open fracture Gustilo-Anderson type I-III A treated by unreamed intramedullary static inter locking nail were selected, while patients with comorbidities,associated intra articular fractures, infection and Gustilo-Anderson type III B-C were  excluded. Patients were operated with intramedullary interlocking and along with wound management. Some required reconstruction with flaps and dynamization of nail. Patients wereclinically and radiographically followed up for union of fracture on monthly interval for 9 months and documented on proforma. SPSS 20 was used for statistical analysis. Results: 70 patients were selected. Males were 60 (85.71%) and females were 10 (14.29%). Mean age was 35.3 Â± 12.8. 32 (45.7%) patients had Gustilo-Anderson type I fracture, 24 (35.2%) had type II fracture and type III-A in 14 (20%) patients. 61(87.14%) patients had duration of fracture 3 or less days and 9 (12.86%) had duration of more than 3 days at presentation. Union occurred in 60patients (85.71 %), Non-union in 10(14.29%) patients. Mean duration of union of fracture was 16.24 Â± 4.19 weeks. 20(28.57%) patients required dynamization of nail. 9(12.85%) patients developed delayed wound and bone infection requiring management.. Conclusion: Intramedullary static unreamed Interlocking Nail is a suitable treatment, and could be preferred treatment in tibial diaphyseal open Gustilo-Anderson Type I-III A fractures, due to achieving timely union and low infection rate. Key words: Tibia, static interlocking nail, diaphyseal open fracture, non-union